The evolving landscape of COVID-19: factors associated with in-hospital COVID-19 related mortality during the 2023–2024 phase of JN.1 subvariant dominance - Drieda Zaçe; Albiana Çekrezi; Christopher Jones; Ludovica Ferrari; Giuseppe De Simone; Elisabetta Teti; Vincenzo Malagnino; Marco Iannetta; Loredana Sarmati; Anna Maria Geretti (BMC Infectious Diseases, 2025)
Abstract Background COVID-19 remains a complex health challenge. We analysed the characteristics and outcomes of COVID-19-related hospitalisations during JN.1 variant dominance. Methods Conducted in a hospital serving a socioeconomically deprived population, this study included all adults hospitalised with COVID-19 from 1st November 2023 to 31st August 2024. The primary outcome was in-hospital mortality, analysed in relation to demographic, clinical, and laboratory parameters. Results Among 122 individuals (median age 76 years, 58.2% males, median comorbidity index 5), 114/122 (93.4%) had received ≥ 1 SARS-CoV-2 vaccination, with a median of 23 months elapsed since the last dose. Fever (67/122, 54.9%) and dyspnoea (49/122, 40.2%) were common presenting symptoms, with 78/122 (64%) showing CT evidence of SARS-CoV-2 pneumonia; 25/122 (20%) had purely neurological presentations. Treatment included remdesivir (115/122, 94.3%) and/or nirmatrelvir/ritonavir (9/122, 7.4%), sotrovimab (15/122, 12.3%), corticosteroids (61/122, 50.0%), and oxygen supplementation (76/122, 62.3%). Whereas 107/122 (87.7%) were discharged after a median of seven days, in-hospital mortality was 15/122 (12.3%) after a median of 16 days. Baseline factors associated with mortality were neutrophil-lymphocyte ratio > 8, D-dimer ≥ 1800 ng/mL, procalcitonin ≥ 1.0 ng/mL, and albumin < 3.2 g/dL; during admission, nasopharyngeal SARS-CoV-2 antigen positivity persisting for > 12 days, hospitalisation for ≥ 10 days, higher oxygen requirements with the resulting corticosteroid use, and healthcare-associated bacteraemia were associated with increased odds of mortality. Conclusions Baseline laboratory parameters and persistent SARS-CoV-2 antigen positivity despite antiviral therapy offer readily available prognostic insights for patients hospitalised with COVID-19. It is imperative to advocate for up-to-date COVID-19 vaccination among older people and other vulnerable groups.